THE REPRESENTATION OF BEAUTY DISCOURSE IN LORD BYRON’S SELECTED POEMS REPRESENTASI WACANA KECANTIKAN DALAM PUISI LORD BYRON - Suryandari, Anisa Hikmah (PARAFRASE : Jurnal Kajian Kebahasaan & Kesastraan, 2019)
This study discusses beauty discourse in the era of Romanticism. Beauty discourse was produced through Byron poems from 1813-1815. Byron was one of the leading figures in the Romantic movement who was influential at the time. We use three Byron poems as the main data for this study. These poems are She Walks in Beauty (1814), Sonnet to Genevra (1813), and Stanzas for Music (1815). The concept of beauty produced by the three poems above connects physical beauty and intellectual beauty with natural elements as one of the great themes of the Romanticism era. The concept of beauty at that time was closely related to the romantic society of England. Referring to this reason, Stuart Hall's representation theory and discursive approach by Michel Foucault are used as a tool to analyze the above problems. The results of this study indicate that the concept of beauty in the romantic era (1) emphasizes intellectual beauty or beyond the physical itself as a concept of beauty in that era. In addition, three concepts of beauty, physical beauty, intellectual beauty, and natural beauty will always lead to divine beauty, where all life comes from Him, and (2) The three poems make beauty an instrument to criticize the presence of the industrial revolution at that time which is considered to cause chaos in romantic life.